Introduction to the Special Theme: Pentecostalism and Spiritual Formation. Issue 1 (May 2020) - Chan, Simon
The last thirty years have seen significant developments in Pentecostal studies. Among them are a broader understanding of key Pentecostal symbols such as Spirit baptism, glossolalia, and eschatology; the grounding of Pentecostal experience in the larger spiritual tradition; and the development of pneumatological perspectives on various theological and practical concerns. The articles dealing with spiritual formation from a Pentecostal perspective are examples of some of these new developments.